The ANALISIS KEKUATAN CASE FLOW WATER METER DENGAN MATERIAL POLYVINYL CHLORIDE RIGID MENGGUNAKAN SOLIDWORK - Wira Guna, Tezar; Hestiawan, Hendri; Hanif Fakhrurroja, Hanif (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
The flow water meter case is an additional structure that protects the meter from mechanical damage, corrosion, and other external environmental influences. In its development, the design of the casing used as a protector must consider various aspects, such as ease of installation, and the sustainability of the use of the material. The purpose of this study is to design a flow water meter casing and calculate the distribution of von mises stress, strain, and displacement under axial loading by simulating a flow water meter casing made of rigid polyvinyl chloride (rigid PVC). In the design process, the casing body was designed using Solidwork 2024 software with predetermined dimensions of 67.8 mm in length, 53.38 mm in width, and 58.5 mm in height using an axial loading type of 100 N placed on the casing body with a clamp support type. The results showed that under axial loading, the maximum value of von mises stress was 11.9 MPa, displacement was 0.389 mm, and strain was 0.0018.